ABOUT SOME SIGNS OF PSEUDORADINNULIIY OL TOPOLOGICAL SPACES - Mirzakhanian, N. E. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
This article considers the question of pseudoradiality of topologically homogeneous spaces with the Baire property that are continuous images of σ-compact topological groups, in particular, free topological groups of compacta. The results obtained are applicable to a more specific and natural question: what properties do topologically homogeneous spaces with the Baire property have that are continuously and transiently acted upon by an σ-compact group?
Keywords: pseudoradiality; Baire property; topologically homogeneous spaces